The Concept of Sakinah Family in The Contemporary Muslim Generation - Fauzan, Ahmad; Amroni, Hadi (al-'adalah, 2020)
This research tries to reveal the meaning of the Sakinah family as one of the goals of marriage as described in the Al-Qur'an Surah Ar-Rum (30:21). The aim, in addition to gaining a clear understanding of the substantive meaning of the term, is to obtain concepts that can be applied in modern life. In achieving this goal, the researcher tries to examine a number of opinions of modern interpretive scholars and analyze them using a qualitative descriptive approach. Based on the results of the analysis of a number of ideas from modern commentators, it can be concluded that the Sakinah family is a family in which harmony, peace, and comfort are created, and runs on legal and religious norms. To realize a sakinah family, every prospective married couple needs to prepare for their marriage from an early age, especially those related to moral, material, mental and spiritual abilities, and have a strong commitment to shaping and maintaining family continuity based on the guidelines and rules of religion and society.